Human rights data for everyone: Introducing the Human Rights Measurement Initiative (HRMI). Issue 1 (1st January 2020) - Brook, Anne-Marie; Clay, K. Chad; Randolph, Susan
Abstract: Cross-national quantitative data measuring human rights practices have existed for about four decades. However, those data have yet to gain much traction in the public sphere, leaving human rights advocacy a largely data-free enterprise. We argue that the underutilization of these data is due to (1) a heavy reliance on public documentation alone as an information source, (2) incomplete coverage of the entire list of internationally recognized rights, and (3) the many barriers to data access and understanding faced by those outside of academia. In response to these problems, we introduce the Human Rights Measurement Initiative, a global collaborative project committed to generating the best cross-national, comprehensive human rights data possible through a process of codesign across disciplines and professions and presenting those data in ways that are accessible and useful to academics, practitioners, and everyday people alike.